2010
DOI: 10.3109/15622975.2010.505663
|View full text |Cite
|
Sign up to set email alerts
|

Patients' preference for olanzapine orodispersible tablet compared with conventional oral tablet in a multinational, randomized, crossover study

Abstract: Objectives. The aim of this study was to compare patients’ preference for olanzapine orodispersible tablet (ODT) with oral conventional tablet (OCT). Methods. A 12-week randomized, crossover, multinational, open-label study was conducted to estimate the proportion of patients preferring ODT or OCT. Outpatients with stable schizophrenia on OCT monotherapy were randomly assigned 1:1 to ODT or OCT. Compliance and drug attitude were measured using the Drug Attitude Inventory (DAI-10) and Medication Adherence Form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…On the other hand, the percentage of subjects voluntarily taking medication increased significantly during the follow-up in the group treated with ODT, only. Thus, similar to the results the atypical neuroleptic form used had no significant effect on the patients' attitude towards the treatment [12,21]. It should also be noted that a positive attitude to treatment increased during the follow-up, regardless of the form of atypical neuroleptics used.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, the percentage of subjects voluntarily taking medication increased significantly during the follow-up in the group treated with ODT, only. Thus, similar to the results the atypical neuroleptic form used had no significant effect on the patients' attitude towards the treatment [12,21]. It should also be noted that a positive attitude to treatment increased during the follow-up, regardless of the form of atypical neuroleptics used.…”
Section: Discussionsupporting
confidence: 69%
“…migraine, Parkinson's disease) [7][8][9] . Studies have shown distinct patient preference for ODTs over regular tablets in certain disease conditions [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Of the fifteen clinical studies assessing the efficacy/effectiveness of ODO, two are RCTs: one is a double-blind parallel-arm trial assessing the safety of ODO compared with SOT as its primary objective27 and the other is an open-label crossover study assessing patient preference for ODO compared with SOT 28. Four observational cohort studies have also compared patients taking ODO and SOT 29–32.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Two RCTs27,28 and four prospective cohort studies29–32 compared the efficacy of ODO with SOT. Additionally, one relatively small (N = 38) retrospective open-label study utilized chronological sequential assignment of patients to ODO or SOT and used PANSS to compare the efficacy of these groups 35.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation